Role of VSSC Gene as a Marker of Sarcoptes scabiei Resistance to Permethrin: A Narrative Review - Nidya Ulfa; Gita Dwi Prasasty; Dalilah Dalilah (Jurnal Ners, 2026)
Scabies, a common dermatological condition, poses a growing challenge in disease management because of the increasing reports of treatment failure. This phenomenon is linked to the declining effectiveness of permethrin, which is the recommended first-line scabicidal agent in many countries. To investigate this, a comprehensive literature review was conducted by searching for publications between 2015 and August 2025 in scientific databases, such as PubMed, Cochrane Library, and Web of Science. The focus was on reports of drug resistance in Sarcoptes scabiei infections and the potential of VSSC gene mutations as markers of permethrin resistance. The voltage-sensitive sodium channel (VSSC) gene is a crucial molecular marker for detecting permethrin resistance in S. scabiei. Mutations in this gene can alter the structure of the sodium channel, which is the target of permethrin, thereby reducing its binding affinity and allowing the mites to survive. Consequently, the early identification and monitoring of VSSC gene mutations are crucial. This approach not only enables the rapid detection of resistant S. scabiei populations but also guides the development of more appropriate treatment strategies, such as selecting alternative acaricides or more effective combination therapies. In addition to resistance, this review also identifies other factors causing treatment failure, known as pseudo-resistance.